Zadnji Prospero - Luthar, Oto (Filozofski vestnik, 1993)
On the basis Shakespeares' figures from The Storm the author is trying to show the danger of unification of modern historical thinking
Keywords: filozofija zgodovine; history; teorija; theory; zgodovina; zgodovinopisje